The Legal Position of the KPK as an Independent Anti-Corruption Agency in Indonesia: A Review in Law No. 19 of 2019 and UNCAC - Asis Asis (Universitas Negeri Semarang, 2024)
This study focuses on the KPK as an independent anti-corruption agency in Indonesia; the current situation is becoming more difficult due to the various types of KPK authorities that existed prior to the passage of Law No. 19 of 2019, which was later changed and exacerbated by the KPK's position under the executive clump. This research will answer the following questions: (1) What is the KPK's position as an independent organization (2) How is the legal analysis of anti-corruption institutions based on Law No. 19 of 2019 and the UN Convention Against Corruption A sociolegal approach is used in this study. The findings revealed that, first, the KPK is not independent because it is part of the executive clump. Second, in terms of wiretapping authority, permission from the supervisory board is required. Third, KPK personnel are classified as members of the State Civil Apparatus (ASN). Fourth, there is a potential conflict of interest. Therefore, Law no. 19 of 2019 should be revised.